2022
DOI: 10.1039/d2dt02763a
|View full text |Cite
|
Sign up to set email alerts
|

Uranium oxide hydrate frameworks with Er(iii) or Y(iii) ions: revealing structural insights leading to the low symmetry

Abstract: Two new mixed-valence uranium oxide hydrate frameworks (UOFs), incorporating either Er3+ or Y3+ ions, were successfully synthesised under hydrothermal conditions and characterised with single-crystal X-ray diffraction and a variety of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Some of the previously published UOFs have been reported as existing in a mixed phase system, with the UOF present as the major phase. 23 In exploring the possible reason as to why the frameworktype structure was favoured during the UOF-Cd synthesis, the most apparent conclusion is the solution pH. Past research has shown the influence the solution pH has on the formation of UOH compounds.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some of the previously published UOFs have been reported as existing in a mixed phase system, with the UOF present as the major phase. 23 In exploring the possible reason as to why the frameworktype structure was favoured during the UOF-Cd synthesis, the most apparent conclusion is the solution pH. Past research has shown the influence the solution pH has on the formation of UOH compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the previously published UOFs have been reported as existing in a mixed phase system, with the UOF present as the major phase. 23…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations